2005
DOI: 10.1093/ndt/gfh674
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of home haemodialysis patients: a case-cohort study

Abstract: Background. Randomized, controlled comparisons between home haemodialysis (HHD) and centre haemodialysis (CHD) have not been performed to date. Reported survival benefits of HHD as compared with CHD from uncontrolled studies have been attributed largely to patient selection. Methods. In order to minimize a selection bias, we have compared the outcome of our HHD and CHD patients with a nested case-cohort study. For each patient trained for HHD at our dialysis centre between 1970 and 1995 (n ¼ 103), a correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 21 publications
5
54
1
4
Order By: Relevance
“…We found that a similar relative risk of death between the PD patient and out-of center patients. In contrast to previous studies [3,5,10,13,14], we found no consistent association between out-of-center HD and better patient survival as compared with in-center HD. In fact, the relative risk of death among patients initiating out-of-center HD was significantly higher compared to those initiated on in-center HD.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that a similar relative risk of death between the PD patient and out-of center patients. In contrast to previous studies [3,5,10,13,14], we found no consistent association between out-of-center HD and better patient survival as compared with in-center HD. In fact, the relative risk of death among patients initiating out-of-center HD was significantly higher compared to those initiated on in-center HD.…”
Section: Discussioncontrasting
confidence: 99%
“…Home hemodialysis (HD) was first introduced in 1964 [1], and its use in the United States peaked in the 1970s [2] when 40% of prevalent patients with end-stage renal disease (ESRD) were treated at home [3]. Unfortunately, the utilization of home HD subsequently declined due to reimbursement issues, complicated HD technology, lack of home HD expertise and training programs, and the concept that adequate dialysis could be achieved with conventional HD [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on mortality and survival had the highest quality score of all outcome data assessed in this review (Table 2; score: 17 out of 31), and included one randomized controlled trial [2] and 9 retrospective or prospective observational studies [3-11], an analysis of an observational study [12], a post-trial observational study of the long-term effects of a randomized controlled trial [13], and a recently published matched-cohort study [14]. Studies predominantly reported positive (9) effects of HHD on mortality or survival compared to ICHD; 2 studies showed negative or no effects.…”
Section: Resultsmentioning
confidence: 99%
“…29 The ability to teach patients to perform their own HD at home has been associated with improved survival and quality-of-life outcomes during traditional home HD. 31,32 Therefore, it is still a worthwhile exercise to teach patients to dialyze at home even if they are only willing to use a standard HD prescription.…”
Section: Outcome Datamentioning
confidence: 99%